The Role of Followers in the Charismatic Leadership Process: Relationships and Their Consequences - Howell, Jane M.; Shamir, Boas (Academy of Management Review, 2005)
We present a theoretical analysis of the follower's role in the charismatic leadership process. Specifically, we distinguish between two types of charismatic relationships—personalized and socialized—and present general propositions about how followers' self-concepts may determine the type of charismatic relationship they form with the leader. We then develop more specific propositions about the follower's role in various stages of the charismatic relationship process, and we conclude by outlining the implications of the propositions and suggesting further opportunities for theoretical extension.